Azathioprine and 6-mercaptopurine-induced intrahepatic cholestasis of pregnancy: Case report and review of the literature - Maya Frank Wolf; Ronen Sloma; Luiza Akria; Eli Rimon; Yifat Wiener; Michal Carmiel Haggai; Lior Lowenstein (Taiwanese Journal of Obstetrics & Gynecology, 2023)
Objective: Azathioprine, a prodrug of 6-mercaptopurine (6-MP), is used in the treatment of inflammatory bowel disease and may be continued during pregnancy. Acute cholestatic liver injury has been reported to occur with azathioprine. We aimed to examine azathioprine related cholestasis effect on pregnancy complications and outcome. Case report: We present a unique case of 6-MP-induced severe intrahepatic cholestasis of pregnancy (ICP) that required meticulous combined therapy including plasma exchange. The symptoms resolved following 6-MP withdrawal. A literature review revealed 11 pregnancies complicated by early-induced severe ICP among women treated with azathioprine or 6-MP. Conclusion: We recommend weekly bile acid level tests for pregnant women treated with azathioprine or 6-MP, beginning early in the second trimester of pregnancy, and the prompt discontinuation of treatment upon establishment of an ICP diagnosis.